Pengembangan Potensi Desa Agrowisata di Desa Sumberagung, Kapanewon Jetis, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Pratama, Yohanes Mario (Jurnal Atma Inovasia, 2023)
This community service program was carried out in Sumberagung Village, Kapanewon Jetis, Bantul Regency, Yogyakarta Special Region Province. Sumberagung Village has various agricultural potentials that can be utilized to increase the income of rural communities such as rice, corn, and cassava. To develop this potential, a program will be carried out to develop agricultural land with the concept of agro-tourism. Later, tourists who come to visit Sumberagung Village agrotourism can see the process of planting and harvesting rice, corn, and cassava plants. Existing data and information were obtained through the official website of Sumberagung Village, internet media, journal articles, and others. The results of the program obtained are the existence of an agro-tourism design in Sumberagung Village which consists of motorbike parking lots, toilets, pavilions, retail sales and flour production houses, as well as a prayer room. In addition, it is also explained how to make rice flour, corn, and cassava. Villagers are expected to be able to implement it so as to increase income and advance Sumberagung Village. The potentials that exist in Sumberagung Village can certainly be developed by requiring the support of the entire community and the local village government.